Exchange-Rate Unification with Black Market Leakages : Russia 1992 - Goldberg, Linda (Washington, D.C. : International Monetary Fund, 1993)
In 1992 Russia unified the multiple exchange rates that had applied to international transactions. This paper describes the multiple exchange rate system that existed in Russia prior to mid-1992 and undertakes a theoretical exploration of the effects of the exchange rate unification that took place in July 1992. The model developed here allows for leakages between official and black markets and permits flexibility of the exchange rates in both official and parallel currency markets. Within this multiple exchange rate system with black market leakages, we trace the dynamic effects on official and parallel foreign exchange markets of changes in the types of policy instruments associated with Russia's exchange rate regime reform. These instruments include adjustments of pegged interbank market exchange rates, rates of foreign exchange surrender taxation, and rates of taxation of capital account transactions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet